Identification of a C3bi-specific membrane complement receptor that is expressed on lymphocytes, monocytes, neutrophils, and erythrocytes - Ross, GD (The Rockefeller University Press, 1982)
Cells expressing a membrane C receptor (CR(3)) specific for C3b-inactivator- cleaved C3b (C3bi) were identified by rosette assay with C3bi-coated sheep erythrocytes (EC3bi) or C3bi-coated fluorescent microspheres (C3bi-ms). C3bi- ms, probably because of their smaller size, bound to a higher proportion of cells than did EC3bi. C3bi-ms bound to greater than 90 percent of mature neutrophils, 85 percent of monocytes, 92 percent of erythrocytes, and 12 percent of peripheral blood lymphocytes. Binding of C3bi-ms to neutrophils, monocytes, and erythrocytes was inhibited by fluid-phase C3bi, Fab anti-C3c, or Fab anti-C3d but was not inhibited by F(ab’)(2) anti-CR(1) (C3b receptor) or F(ab’)(2) anti-CR(2) (C3d receptor) nor by fluid-phase C3b, C3c, or C3d. This indicated that monocytes, neutrophils, and erythrocytes expressed C3bi receptors (CR(3)) that were separate and distinct from CR(1) and CR(2) and specific for a site in the C3 molecule that was only exposed subsequently to cleavage of C3b by C3b inactivator and that was either destroyed, covered, or liberated by cleavage of C3bi into C3c and C3d fragments. Lymphocytes differed from these other cell types in that they expressed CR2 in addition to CRa. Lymphocyte C3bi-ms rosettes were inhibited from 50 to 84 percent by F(ab’)(2)-anti-CR(2) or fluid-phase C3d, whereas C3d-ms rosettes were inhibited completely by F(ab’)(2) anti-CR(2), fluid-phase C3bi, or fluid- phase C3d. Thus, with lymphocytes, C3bi was bound to CR(3), and in addition was bound to CR(2) by way of the intact d region of the C3bi molecule. In studies of the acquisition of C receptors occurring during myeloid cell maturation, the ability to rosette with C3bi-coated particles was detected readily with immature low-density cells, whereas this ability was nearly undetectable with high density mature polymorphonuclear cells. This absence of C3bi binding to polymorphs was not due to a loss of the CR(3) but instead was due to the maturation-linked acquisition of the abiity to secrete elastase that cleaved reagent particle-bound C3bi into CR(3)-unreactive C3d. Neither neutrophils nor monocytes bound C3d-coated particles at any stage of maturation. Assay of CR(3) with mature neutrophils required inhibition of neutrophil elastase with either soybean trypsin inhibitor or anti-elastase antibodies, and the amounts of these elastase inhibitors required to allow EC3bi rosette formation increased with neutrophil maturation. Because lymphocytes bound C3bi to CR(2) as well as to CR(3), specific assay of lymphocyte CR(3) required saturation of membrane CR(2) with Fab’ anti-CR(2) before assay for rosettes with C3bi-ms. Only 3.5 percent of anti-CR(2)- treated peripheral blood lymphocytes bound C3bi-ms. Therefore, among normal blood lymphocytes the majority of the 12 percent C3bi-ms-binding cells expressed only CR(2) (8.5 percent), and the small proportion of C3bi-ms- binding cells that expressed CR(3) (3.5 percent) represented a distinct subset from the CR2(+) cells. Double-label assay indicated that 3.0 percent out of 3.5 percent of these CR(3)-bearing lymphocytes were B cells because they expressed membrane immunoglobulins. Of the remaining CR(3)(+) cells, 0.2 percent expressed either Leu-1 or 3A1 T cell antigens, and 0.6 percent expressed the OKM-1 monocyte-null lymphocyte determinant.